Sustainable and Resilient Supply Chains Using Emerging Technologies: Policy Options: Proceedings of a Workshop–in Brief - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The coronavirus disease 2019 (COVID-19) crisis sparked concerns about the vulnerability of supply chains and the significant impact of their disruption on the economy and society within the U.S. and abroad. Issues around global supply chains existed before the pandemic but were also greatly aggravated by it. To consider these issues, the Science and Technology for Sustainability program, in collaboration with the Resilient America Program, Transportation Research Board, and Board on Atmospheric Sciences and Climate at the National Academies of Sciences, Engineering, and Medicine, held a series of four virtual workshops on February 3, 4, 17, and 18, 2021. The workshop series addressed opportunities, challenges and environmental implications of increasing local inclusion and community participation in global value chain networks by using new technologies to strengthen resilience and sustainability in the face of recurring disruptions. The series also explored the feasibility of introducing advanced manufacturing, logistics and decision-making under alternative supply chain scenarios in different sectors, with a view to strengthening the resilience of communities and adopting far more environmentally and economically sustainable consumption and production approaches. This publication summarizes the presentations and discussion of the workshops.
Keywords: Environment and Environmental Studies

Climate-Resilient Supply Chains: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
As the COVID-19 pandemic has demonstrated, the global supply chain is vulnerable to major disruptions from unanticipated events, yet no threat to the functioning of essential supply chains looms larger than the growing number of extreme weather events resulting from climate change. Indeed, the characteristics of today's supply chains - their dependence on shipping and air transport, specialized inputs sourced from specific locations spread worldwide, and reduced inventories tied to just-in-time production - make them especially vulnerable to disruption from climate risks. With the goal of protecting global trade worth almost $20 trillion annually against such disruptions, supply chain executives and researchers who study global supply chains are now starting to focus on ways of increasing supply chain resilience in a world buffeted by climate change. To explore ongoing efforts to create climate-resilient supply chains, the Science and Technology for Sustainability program at the National Academies of Sciences, Engineering, and Medicine, held a two-day virtual workshop on September 27-28, 2021.
Keywords: Environment and Environmental Studies

Addressing Supply Chain and Manufacturing Challenges and Opportunities: Proceedings of a Workshop Series–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The COVID-19 pandemic escalated supply chain vulnerabilities that affect almost every sector of the economy. Identifying key vulnerabilities and developing responses to them will require the mobilization of diverse actors across the U.S. research enterprise. In October and November 2021, the Government-University-Industry Research Roundtable (GUIRR) of the National Academies of Sciences, Engineering, and Medicine convened a number of virtual workshops for its membership and invited guests to discuss opportunities for enhancing U.S. approaches to addressing manufacturing and supply chain resilience, security, and sustainability challenges through partnerships and cross-sector collaboration. In convening experts and leaders from across sectors and disciplines, GUIRR provided a forum for dialogue on policy priorities for consideration by leaders across the research enterprise. This publication summarizes the presentation and discussion of the workshop series.
Keywords: Industry and Labor

Strengthening Post-Hurricane Supply Chain Resilience: Observations from Hurricanes Harvey, Irma, and Maria - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Resilient supply chains are crucial to maintaining the consistent delivery of goods and services to the American people. The modern economy has made supply chains more interconnected than ever, while also expanding both their range and fragility. In the third quarter of 2017, Hurricanes Harvey, Irma and Maria revealed some significant vulnerabilities in the national and regional supply chains of Texas, Florida, the U.S. Virgin Islands, and Puerto Rico. The broad impacts and quick succession of these three hurricanes also shed light on the effectiveness of the nation's disaster logistics efforts during response through recovery. Drawing on lessons learned during the 2017 hurricanes, this report explores future strategies to improve supply chain management in disaster situations. This report makes recommendations to strengthen the roles of continuity planning, partnerships between civic leaders with small businesses, and infrastructure investment to ensure that essential supply chains will remain operational in the next major disaster. Focusing on the supply chains food, fuel, water, pharmaceutical, and medical supplies, the recommendations of this report will assist the Federal Emergency Management Agency as well as state and local officials, private sector decision makers, civic leaders, and others who can help ensure that supply chains remain robust and resilient in the face of natural disasters.
Keywords: Conflict and Security Issues; Earth Sciences

Globally Resilient Supply Chains for Seasonal and Pandemic Influenza Vaccines - National Academies of Sciences, Engineering, and Medicine; National Academy of Medicine (The National Academies Press, 2022)
Influenza viruses, both seasonal and pandemic, have the potential to disrupt the health and well-being of populations around the world. The global response to the COVID-19 pandemic and prior public health emergencies of international concern illustrate the importance of global preparedness and coordination among governments, academia, scientists, policy makers, nongovernmental organizations, the private sector, and the public to address the threat of pandemic influenza. These health emergencies have revealed opportunities to enhance global vaccine infrastructure, manufacturing, distribution, and administration. Globally Resilient Supply Chains for Seasonal and Pandemic Influenza Vaccines outlines key findings and recommendations to bolster vaccine distribution, manufacturing, and supply chains for future seasonal and pandemic influenza events. This report addresses the challenges of manufacturing and distributing vaccines for both seasonal and pandemic influenza, highlighting the critical components of vaccine manufacturing and distribution and offering recommendations that would address gaps in the current global vaccine infrastructure.
Keywords: Health and Medicine

Impact of the Global Medical Supply Chain on SNS Operations and Communications: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The Centers for Disease Control and Prevention (CDC) established the Strategic National Stockpile (SNS) with a focus on procuring and managing medical countermeasures (MCM) designed to address chemical, biological, radiological, and nuclear events and attacks by weapons of mass destruction. The stockpile is a repository of antibiotics, chemical antidotes, antitoxins, vaccines, antiviral drugs, and other medical materiel organized to respond to a spectrum of public health threats. Over time, the mission of the SNS has informally evolved to address other large-scale catastrophes, such as hurricanes or outbreaks of pandemic disease, and rare acute events, such as earthquakes or terror attacks. When disaster strikes, states can request deployment of SNS assets to augment resources available to state, local, tribal, or territorial public health agencies. CDC works with federal, state, and local health officials to identify and address their specific needs and, according to the stated mission of the SNS, ensure that the right resources reach the right place at the right time.
Keywords: Health and Medicine

Making U.S. Ports Resilient as Part of Extended Intermodal Supply Chains - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Freight Research Program (NCFRP) Report 30: Making U.S. Ports Resilient as Part of Extended Intermodal Supply Chains focuses on identifying and elaborating on the steps needed to coordinate freight movements through ports in times of severe stress on existing operating infrastructures and services.This report builds on NCHRP Report 732: Methodologies to Estimate the Economic Impacts of Disruptions to the Goods Movement System to provide a set of high-level guidelines to help seaport authorities with minimizing lost throughput capacity resulting from a major disruption.
Keywords: Transportation and Infrastructure

Freight Transportation Resilience in Response to Supply Chain Disruptions - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Guidance to public and private stakeholders on mitigating and adapting to logistical disruptions to supply chains resulting from regional, multi-regional, and national adverse events, both unanticipated and anticipated, is provided in NCFRP (National Cooperative Freight Research Program) Research Report 39: Freight Transportation Resilience in Response to Supply Chain Disruptions.The report makes a significant contribution to the body of knowledge on freight transportation and system resiliency and also includes a self-assessment tool that allows users to identify the current capability of their organization and institutional collaboration in preparing for and responding to supply chain disruptions.Disruptions to the supply chain and their aftermath can have serious implications for both public agencies and companies. When significant cargo delays or diversions occur, the issues facing the public sector can be profound. Agencies must gauge the potential impact of adverse events on their transportation system, economy, community, and the resources necessary for preventive and remedial actions, even though the emergency could be thousands of miles away.Increasing temporary or short-term cargo-handling capacity may involve a combination of regulatory, informational, and physical infrastructure actions, as well as coordination across jurisdictional boundaries and between transportation providers and their customers. For companies, concerns can include such issues as ensuring employee safety, supporting local community health, maintaining customer relationships when products and goods are delayed, and ultimately preserving the financial standing of the company.
Keywords: Transportation and Infrastructure

The Security of America's Medical Product Supply Chain: Considerations for Critical Drugs and Devices: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Recent disasters and health emergencies, including the COVID-19 pandemic, have shed light on the fragility of the U.S. medical supply chain and underscored the need to explore policy, regulatory, and systems solutions to prevent and mitigate the impacts of shortages on public health, national security, and patient care. Under the Coronavirus Aid, Relief, and Economic Security (CARES) Act, the National Academies of Sciences, Engineering, and Medicine established an ad hoc committee to examine the security and resilience of the U.S. medical product supply chain. Specifically, the committee was asked to assess and evaluate the impact of U.S. dependence on critical drugs and devices sourced or manufactured outside the U.S. and provide recommendations to improve the resilience and address the vulnerabilities of the medical supply chain. On December 1 and 2, 2020, the Committee on Security of America's Medical Product Supply Chain held a two-day virtual public workshop focused on assessing lists of critical and essential medical products. The workshop sought to conceptually explore how critical and essential medical product lists are developed and used in practice. The committee's consensus study report will be available in 2022. This Proceedings of a Workshop-in Brief summarizes the discussions that occurred at the workshop.
Keywords: Health and Medicine